Propofol Inhibits Proliferation and Augments the Anti-Tumor Effect of Doxorubicin and Paclitaxel Partly Through Promoting Ferroptosis in Triple-Negative Breast Cancer Cells - Sun, Chen; Liu, Pan; Pei, Lijian; Zhao, Mengyun; Huang, Yuguang (Frontiers in Oncology, 2022)
Background: Triple-negative breast cancer (TNBC) is relatively common in women and is associated with a poor prognosis after surgery and adjuvant chemotherapy. Currently, the mechanism underlying the relationship between propofol and breast cancer is controversial and limited to cell apoptosis. Moreover, there are only a few studies on the effect of propofol on the chemotherapeutic sensitivity of TNBC cells. Therefore, this study explored whether propofol and its commonly used clinical formulations affect the proliferation and chemotherapeutic effects on TNBC cells by regulating cell ferroptosis. Methods: We selected MDA-MB-231 cells, and the effects of propofol, propofol injectable emulsion (PIE), or fospropofol disodium, alone or combined with doxorubicin or paclitaxel on cell viability, apoptosis, intracellular reactive oxygen species (ROS) accumulation, ferroptosis-related morphological changes, intracellular Fe2+ levels, and the expression and localization of ferroptosis-related proteins were investigated. Results: We found that propofol significantly inhibited MDA-MB-231 cell proliferation, and all three propofol formulations augmented the anti-tumor effects of doxorubicin and paclitaxel. The results from the ROS assay, transmission electron microscopy, intracellular Fe2+ assay, western blotting, and multiplex immunohistochemistry revealed that propofol not only induced apoptosis but also triggered ferroptosis-related changes, including morphological changes of mitochondria, increased intracellular ROS levels, and intracellular iron accumulation in MDA-MB-231 cells. The ferroptosis-related p53-SLC7A11-GPX4 pathway was also altered under different treatment propofol, doxorubicin, or paclitaxel regimens. Conclusion: Propofol showed anti-proliferation effects on TNBC cells and could be a potential adjuvant to enhance the chemotherapeutic sensitivity of TNBC cells partly by promoting cell ferroptosis.